The new Jim Crow : mass incarceration in the age of colorblindness - Alexander, Michelle (New Press, 2020)
"Seldom does a book have the impact of The New Jim Crow. Since it was first published in 2010, it has been the winner of numerous awards and has spent nearly 250 weeks on the New York Times bestseller list. It has been cited in judicial decisions, read in countless faith-based and secular book clubs, and adopted in campus-wide and community-wide reads. Most important, it has inspired artists, philanthropists, policymakers, community leaders, and a whole generation of racial justice activists motivated by Michelle Alexander's searing indictment of our criminal justice system and her unforgettable argument that 'we have not ended racial caste in America; we have merely redesigned it'"--Back cover.